Assessment of a-priori and dynamic extended learner profiling for accommodative learning - Allan J. Pellow; Elaine M. Smith; Barry J. Beggs; Hernando L. Fernandez-Canque (2005)
Undergraduates often have experiences during their period of study that can have adverse effects on their ability to complete a particular course. This paper describes the use of an online questionnaire to integrate an exploration of learning styles, as presented by Felder and Silverman in 1988, with an investigation of additional student risk factors. The report demonstrates the complexity of marking and evaluating the validity of such studies, be they online, or in paper formats. It also investigates a method of evaluating the data before committing the evaluation technique to software. The learning styles utilised are; Visual/Verbal/Kinaesthetic and Global/Sequential. The information gathered about learning styles can inform and stimulate tutor reflection on suitable teaching styles. The risk factors considered include; academic expectations, subject interest, ability to understand, examination nervousness, mathematical ability and age. The ability to define referred learning styles and learner risk factors results in the creation of individual Learner Profile. Information stored on an online database as the questionnaire responses are uploaded. It also gives an overall impression of the learning styles and the risk factors of the individual and of the cohort. Risk factors can also be considered as support requirement indicators. The investigation reported in this paper forms part of a continuing philosophy of student support which has been successfully employed within the School of Engineering Science and Design at Glasgow Caledonian University for some time. This process of support, known as the ‘Triple C’ model (standing for care, control and consistency) has dramatically increased the retention and progression of first year undergraduates to second year over the last three academic years.